Legal Politics and Human Rights Development in Indonesia - Abdullah, Abdullah; Lala , Andi (Riviera Publishing, 2025)
This research aims to examine in depth the relationship between legal politics and the development of human rights (HAM) in Indonesia in the context of legal dynamics and state governance. The research method used is qualitative descriptive, with a literature study approach to laws and regulations documents, Constitutional Court decisions, scientific journals, and reports of national and international human rights institutions. The results of the study show that since the reform era, Indonesia's legal politics has undergone significant changes marked by the birth of various policies and regulations that support human rights protection, such as the ratification of human rights laws, the ratification of various international conventions, and the establishment of independent oversight institutions. However, the implementation of these rights on the ground still faces various challenges, including weak law enforcement, overlapping regulations, and the dominance of political interests in the legislation process. Therefore, legal reform is needed that not only focuses on regulation alone, but also on the formation of a legal culture that favors the values of justice, democracy, and respect for human dignity.